Analisis Pembiayaan Murabahah Untuk Kesejahteraan Karyawan Di BMT LKK UMSU - Sari, Ratih Namira; Rahmayati, Rahmayati (-, 2023)
This study was conducted with the aim of analyzing murabahah financing in the welfare of employees at BMT LKK UMSU. This research is obtained on the assumption that with murabahah financing can improve employee welfare. This research method uses qualitative research with the type of case study research. Data collection techniques used in this study were observation, interviews and documentation. Based on the result of research and analysis of Key data that with this murabahah financing can improve the welfare of employess at BMT LKK UMSU.